The Tourism Adaptation Classification (TAC) framework: An application to New Zealand's Glacier country - Strong, Samantha; Stewart, Emma J.; Espiner, Stephen; Hanly, Katherine (Frontiers in Human Dynamics, 2023)
Alongside growing awareness of the significance of environmental change for glacier regions, and their tourism-dependent communities, is the realization of the need to adapt to changing conditions. Such adaptation is necessary for tourism operators, managers, and planners as well as the visitors themselves, and is part of building resilient tourism systems. Following Pelling (2010) and Salim et al. (2021a), this paper presents a conceptual framework for understanding the possible stages of adaptation in glacier tourism destinations. The Tourism Adaptation Classification (TAC) framework aligns an interpretation of Pelling’s three ‘visions of adaptation’ (resilience, transition, and transformation) against a consolidation of Salim et al’s. (2021a) adaptation strategies implemented by tourism stakeholders, and identifies specific characteristics. Using a desk-based case study approach, the framework is illustrated with reference to Glacier Country in New Zealand’s Westland/Tai Poutini National Park in relation to three core dimensions of the tourism system: tourism planning and governance; tourism business and operations; and visitor experience.